Pengaruh DPK, Pembiayaan Mudharabah, Musyarakah, Murabahah, dan Ijarah Terhadap Kinerja Keuangan dengan NPF Sebagai Variabel Moderasi Pada Bank Umum Syariah - Galuh Andini Novarina; Dimas Emha Amir Fikri Anas; Mochamad Fariz Irianto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of Third Party Funds (DPK), Mudharabah Financing, Musyarakah, Murabahah, and Ijarah on the financial performance of Indonesian Islamic banks, using Non-Performing Financing (NPF) as a moderating variable. This study employs a quantitative approach using secondary data obtained from the fourth-quarter financial reports of Indonesian Islamic banks for the period 2021–2023. The sampling technique used is purposive sampling, and the data is analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results of the study indicate that Musyarakah and Murabahah financing influence financial performance measured by Return on Assets (ROA), while TFD, Mudharabah, Ijarah, and NPF do not influence financial performance measured by Return on Assets (ROA). However, NPF can moderate the relationship between DPK, Musyarakah, and Murabahah financing and financial performance, but does not moderate Mudhrabah and Ijarah financing. This study highlights the importance of managing credit risk in enhancing the effectiveness of financing schemes in Islamic banking. This study also confirms that not all types of Islamic financing contracts contribute equally to financial performance, and their impact may depend on the bank's ability to prevent financing risks through effective NPF control. This study contributes to the understanding of how certain financing mechanisms, when moderated by credit risk indicators, can affect the profitability and financial sustainability of Islamic banks in Indonesia. This study suggests that Islamic banks should strengthen their risk management frameworks, particularly in monitoring NPF, and focus on optimizing Musyarakah and Murabahah financing to improve financial outcomes.